2011
DOI: 10.3168/jds.2010-3914
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism of 2-hydroxy-4-(methylthio)butanoate (HMTBA) in lactating dairy cows

Abstract: The objectives of the current study were to determine the fate and contribution to Met kinetics of 2-hydroxy-4-(methylthio)butanoate (HMTBA) at the whole-body, splanchnic, and mammary levels. Four multicatheterized cows (31.3 kg of milk/d; 17.7 kg of DMI/d) were used in a crossover design, with two 1-wk periods, to determine the metabolic fate of HMTBA and its effect on Met metabolism. Over the last 2 d of each period, cows were infused, via a jugular vein, with saline or HMTBA (Alimet, Novus International Inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 28 publications
0
19
1
1
Order By: Relevance
“…More recent data by Uchida et al (2003) and Noftsger et al (2005), however, indicated no effect of HMTBa on milk production and composition. Similarly, Rulquin et al (2006), Johnson-VanWieringen et al, (2007), and Lapierre et al (2011) did not find any production effects of HMTBa or a combination of HMTBa and Lys-HCl in cows fed basal diets with 15.3 to 19.5% CP. Similar lack of effect of HMTBa on DMI and milk yield was recently reported by Baldin 2014).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…More recent data by Uchida et al (2003) and Noftsger et al (2005), however, indicated no effect of HMTBa on milk production and composition. Similarly, Rulquin et al (2006), Johnson-VanWieringen et al, (2007), and Lapierre et al (2011) did not find any production effects of HMTBa or a combination of HMTBa and Lys-HCl in cows fed basal diets with 15.3 to 19.5% CP. Similar lack of effect of HMTBa on DMI and milk yield was recently reported by Baldin 2014).…”
Section: Resultsmentioning
confidence: 79%
“…The bioavailability of HMTBa relative to that of dl-Met has been extensively studied with reports in the literature of 60 to 80% (depending on the function: BW gain, feed conversion, breast meat yield) in broiler chicken (Zelenka et al, 2013) and several meta-analyses have reported bioavailability of 81 to 100% in poultry (Vazquez-Añon et al, 2006;Vedenov and Pesti, 2010). A recent study with 13 C-labeled HMTBa infused intravenously demonstrated that the compound can serve as a source of Met and also has a Met-sparing effect in dairy cows, with 15% of the milk protein Met originating from direct conversion of HMTBa to Met (Lapierre et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al () reported that HMB decreased dietary crude protein digestibility and increased microbial N outflow from the rumen. The study with 13 C‐labeled HMB infused intravenously showed that the Met analog can serve as a source of Met and also has a Met‐sparing effect in dairy cows, with 15% of the milk protein Met originating from direct conversion of HMB to Met (Lapierre et al ). It is inferred that HMB as a rumen‐protected Met can increase concentration of rumen MCP and milk protein potentially by releasing Met in the intestine.…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis conducted by Zanton et al (2014) discovered an increase in percent milk fat due to HMTBa supplementation, but production responses to HMTBa reported in the literature varied significantly across studies. Multiple studies have indicated no effect on milk production or milk composition Lapierre et al, 2011;Lee et al, 2015), while others saw boosts in percent milk fat (Lundquist et al, 1985;Hansen et al, 1991;Baldin et al, 2018), or milk yield (Piepenbrink et al, 2004;Wang et al, 2010). The conflicting results across studies can be attributed to a variety of factors including but not limited to the level of inclusion rate of HMTBa, day of sample relative to parturition, success/failure in truly meeting daily dietary nutrient requirements, and the variation in metabolism and milk production between dairy and beef cows.…”
Section: Milk Compositionmentioning
confidence: 99%